PRb2/p130 Localizes to the Cytoplasm in Diffuse Gastric Cancer. Issue 4 (April 2015) - Cito, Letizia; Indovina, Paola; Forte, Iris Maria; Pentimalli, Francesca; Di Marzo, Domenico; Somma, Pasquale; Barone, Daniela; Penon, Antonella; Penon, Danila; Ceccherini, Elisa; Micheli, Pietro; Saragoni, Luca; et al.
Abstract pRb2/p130 is a key tumor suppressor, whose oncosuppressive activity has mainly been attributed to its ability to negatively regulate cell cycle by interacting with the E2F4 and E2F5 transcription factors. Indeed, pRb2/p130 has been found altered in various cancer types in which it functions as a valuable prognostic marker. Here, we analyzed pRb2/p130 expression in gastric cancer tissue samples of diffuse histotype, in comparison with their normal counterparts. We found a cytoplasmic localization of pRb2/p130 in cancer tissue samples, whereas, in normal counterparts, we observed the expected nuclear localization. pRb2/p130 cytoplasmic delocalization can lead to cell cycle deregulation, but considering the emerging involvement of pRb2/p130 in other key cellular processes, it could contribute to gastric tumorigenesis also through other mechanisms. Our data support the necessity of further investigations to verify the possibility of using pRb2/p130 as a biomarker or potential therapeutic target for diffuse gastric cancer. J. Cell. Physiol. 230: 802–805, 2015. © 2014 Wiley Periodicals, Inc.